High concentrations of radon and carbon dioxide in energy-efficient family houses without heat recovery ventilation - Géczi, Gábor; Benécs, József; Kristóf, Krisztina; Horváth, Márk (Journal of Environmental Engineering and Landscape Management, 2018)
The most significant factors of indoor air quality – besides temperature and humidity – are the concentrations of carbon-dioxide (CO2) and radon (222Rn). Radon seepage is caused by and affected by the materials used in walls and floors, the quality of insulation, cracks and even the amount of pipes running through the walls. The amount of CO2 is predominantly affected by the biological processes of the inhabitants, and possibly by potentially faulty HVAC systems. The energy efficiency related upgrades to family homes, which often only extend to window replacements and better insulation have a significant effect and could potentially increase concentrations of both radon and CO2 which has a significant effect on the well-being of the inhabitants. Our tests conducted in Hungary have proven that by using automated heat recovery ventilation (HRV) both energy efficient operation and low concentrations of radon and CO2 are achievable. Our results prove the significance and prevalence of the issue of higher concentrations of these pollutants, and offer a viable solution.